2006
DOI: 10.1002/ana.21006
|View full text |Cite
|
Sign up to set email alerts
|

Fukutin gene mutations in steroid‐responsive limb girdle muscular dystrophy

Abstract: Our data suggest that fukutin mutations occur outside Japan and can be associated with much milder phenotypes than Fukuyama congenital muscular dystrophy. These findings significantly expand the spectrum of phenotypes associated with fukutin mutations to include this novel form of limb girdle muscular dystrophy that we propose to name LGMD2L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 31 publications
3
80
0
2
Order By: Relevance
“…Wong-Kisielet et al described stabilization and improvement of muscle strength in two siblings with b-SG after 30 months of deflazacort therapy 20 . In other forms of muscular dystrophies there have also been reports of a positive response to corticosteroids [21][22] . Godfrey et al described three children with an LGMD phenotype and pathogenic fukutin mutation that had a remarkable steroid responsiveness 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Wong-Kisielet et al described stabilization and improvement of muscle strength in two siblings with b-SG after 30 months of deflazacort therapy 20 . In other forms of muscular dystrophies there have also been reports of a positive response to corticosteroids [21][22] . Godfrey et al described three children with an LGMD phenotype and pathogenic fukutin mutation that had a remarkable steroid responsiveness 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The remaining patients had no structural brain involvement; one case had CMD-no mental retardation and never acquired the ability to walk but has normal IQ and five individuals from three families have entirely normal intellect and a mild LGMD phenotype (LGMD 2M). Interestingly in the latter two of these families, a dramatic response to steroid therapy was noted (Godfrey et al, 2006).…”
Section: Worldwide Distribution Of Fukutin Mutationmentioning
confidence: 97%
“…Godfrey et al (2006Godfrey et al ( , 2007 reported on five nonJapanese children from three families with normal intelligence and limb-girdle phenotype, caused by heterozygous point mutations in the FKTN gene. Puckett et al (2009) reported an additional two brothers with a LGMD phenotype due to compound heterozygous FKTN mutation.…”
Section: Milder Phenotype Of Fcmdmentioning
confidence: 99%
“…Although no trials have been conducted on glucocorticosteroid treatment in LGMD2I, there is a report of benefit, 93 which has also been seen in LGMD2K. 94 A recent study that looked at the effect of moderate-intensity endurance training showed that it is a safe method to increase exercise performance and daily function in patients with LGMD2I. 95 Exercise studies in other forms of LGMD2 have not yet been systematically performed.…”
Section: Lgmd2 Associated With Secondary Reduction In Alpha Dystroglycanmentioning
confidence: 99%